DAMPAK GEMPA BUMI LOMBOK TERHADAPKONDISI SOSIAL EKONOMI MASYARAKAT DI DESAKEKAIT KECAMATAN GUNUNG SARI KABUPATENLOMBOK BARAT (Sophist: Jurnal Sosial Politik Kajian Islam dan Tafsir, 2018)
This study aims to determine the impact or effect of the Lombok 2018 earthquake on the socio-economic life of the community in Kekait Village, Gunung Sari District, West Lombok Regency and find out the efforts made by the community in Kekait Village, Gunung Sari District, West Lombok Regency to rise from adversity due to the Lombok earthquake 2018 that happened. This study included research using a qualitative descriptive approach with a double embedded case study strategy. Data is taken from primary and secondary data. While the data sources in this study are informants or informants, events and activities as well as documents and archives. Test data validity is done by using data or source triangulation techniques and method triangulation. Data analysis uses interactive data analysis techniques with stages, namely: data collection, data reduction, data presentation, drawing conclusions and verification. The results of the study show that the impact of the earthquake on the Kekait Village community has had a tremendous impact on their lives. The August 5 2018 earthquake has a serious impact, especially the economic paralysis which results in every citizen living in an “invalid capital” situation or living without income at all, which applies to at least three community groups including entrepreneurship, farmers, and laborers. While other impacts of social activities such as social gathering, mutual cooperation, tahlilan and ruwahan in the research area had been halted after the earthquake because there was no room to carry out these activities. Social activities will begin to be implemented again after the reconstruction process is complete. There are three strategies that are carried out by the kepuh community. The link in the effort to rise from the economic downturn includes: First, psychological efforts. Second, religious efforts. Third economic effort.
Keywords: masyarakat; sosial ekonomi; upaya dilakukan; gempa bumi